Cleaning of the surfaces in the food industry using cold plasma - Jovicic, Vojislav; Jung, Isabella; Zbogar-Rasic, Ana; Khan, Muhammad Jehanzaib; Delgado, Antonio (Proceedings der 25. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2017)
UnivIS-Import:2018-09-11:Pub.2017.tech.ITC.stmmec.cleani

Degradation of Low Concentrated Perfluorinated Compounds (PFCs) from Water Samples Using Non-Thermal Atmospheric Plasma (NTAP) - Jovicic, Vojislav; Khan, Muhammad Jehanzaib; Zbogar-Rasic, Ana; Fedorova, Nataliia; Poser, Alexander; Swoboda, Peter; Delgado, Antonio (Energies, 2018)
Perfluorinated compounds (PFCs) are manmade chemicals, containing the covalent C-F bond, which is among the strongest chemical bonds known to organic chemistry. Abundant use of these chemicals contaminates air, water, and soil around the world. Despite recent initiatives and legal regulations set to reduce their omnipresence, conventional water purification processes are either inefficient or very expensive, especially for low PFC contamination levels. This research is focused on the non-thermal atmospheric plasma (NTAP) decomposition of very low concentrations (<1 µg/L) of PFCs (especially perfluorooctanoic acid (PFOA) and perfluorooctanesulfonate (PFOS)), present in the wastewater produced during the process of PFCs removal from contaminated soil. The efficiency of the decomposition process was investigated for air, oxygen, and nitrogen plasma, with exposure times of 1–10 min and different plasma nozzle- and reactor sizes. Experiments demonstrated that the NTAP treatment is an efficient alternative method for degradation of more than 50% of the initial PFC concentration in the water samples, in less than 200 s. The final concentration of PFC showed strong dependency on the tested parameters. The treatment effect showed to be strongly non-linear with time, followed by the reduction of the pH-value of the treated sample, which might present a limiting factor for further PFC decompositio
UnivIS-Import:2018-09-11:Pub.2018.tech.ITC.stmmec.degrad
Keywords: Non-thermal atmospheric plasma; Perfluorinated compound (PFC) removal; Wastewater treatment

Effectiveness of Non-Thermal Plasma Induced Degradation of Per- and Polyfluoroalkyl Substances from Water - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Poser, Alexander; Freichels, Katharina; Delgado, Antonio (Water, 2022)
Per- and polyfluoroalkyl substances (PFAS) are omnipresent synthetic chemicals. Due to their industrial importance and widespread use as a key component in various applications and a variety of products, these compounds can be found today in high concentrations (>1 mu g/L) in surface and groundwater but also spread throughout the ecosystem, where they represent a serious threat to most living organisms. The removal or degradation of PFAS contaminants from water and soil is becoming a legal obligation in a growing number of countries around the globe. This, however, demands novel techniques for the degradation of PFAS since conventional water treatment techniques are either insufficient or extremely expensive due to the persistent nature of these compounds caused by their extraordinary chemical stability. The goal of this work was therefore to investigate the practical potential of the application-oriented use of atmospheric non-thermal plasma as a powerful advanced oxidation method for the purification of water contaminated with PFAS compounds. Special attention was devoted to the development of the concept that can be scaled up to the capacity level of approximately 100-200 m(3) of water per hour, contaminated with PFAS and other contaminants including organic and inorganic material generally present in soil, and surface or groundwater. Our major research interest was to define the minimum required treatment time for optimal purification results, as well as to understand the influence of the initial concentration of PFAS in water and the potential presence of co-contaminants often present in situ on the efficiency of the degradation process. A chemical analysis of the treated samples demonstrated the ability of the atmospheric plasma to reduce more than 50% of the initial PFAS amount in the water samples in less than 300 s of treatment time. PFOA, however, showed more rigidity towards degradation, where a double treatment time was needed to reach similar degradation levels. The obtained results showed that the initial concentration level does not play a major role in the process. However, the PFAS degradation profiles for all tested concentrations show a strongly nonlinear behavior with time, characterized by the fast decrease of the process efficiency in the case of longer treatment times. For prolonged treatment times, a constant increase in the samples' conductivity was measured, which might be the limiting factor for the degradation rate in the case of prolonged treatment times.
CRIS-Team WoS Importer:2022-05-27

Enhancement of Wheat Flour and Dough Properties by Non-Thermal Plasma Treatment of Wheat Flour - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Delgado, Antonio (Applied Sciences, 2022)
Demand to improve food quality attributes without the use of chemicals has risen exponentially in the past few years. Non-thermal plasma (NTP) (also called ‘cold plasma’) is becoming increasingly popular for this purpose due to its unique low-temperature and non-chemical nature. In the present research, the concept of in situ dielectric barrier discharge (DBD) plasma treatment inside a rotational reactor for the direct treatment of wheat flour was experimentally analyzed. The primary research goal was to determine the effects of short-period NTP treatment of DBD type on flour and dough properties. For this purpose, the influence of different operating parameters was tested, i.e., treatment time, the amount of flour placed in the reactor and the environmental (air) temperature. Changes in the structural attributes of the most commonly used flours (type 550 and 1050) and their respective doughs were studied using a set of analytical techniques. Rheological analysis demonstrated the ability of NTP to significantly intensify the visco-elastic properties of dough produced from wheat flour type 550 that was treated for less than 180 s. This indicated that plasma treatment enhanced intermolecular disulphide bonds in gluten proteins, which resulted in stronger protein–starch network formations. However, longer treatment times did not result in a significant increase in the visco-elastic properties of wheat dough. The obtained results showed a 6–7% increase in flour hydration due to NTP treatment, which also makes a contribution to hydrogen bonding due to changes in the bonded and free water phase. Experimental findings further confirmed the dependence of NTP treatment efficiency on environmental air temperature.
CRIS-Team Scopus Importer:2022-09-09
Keywords: dielectric barrier discharge; dough; hydration properties; microstructure; non-thermal plasma; rheology; wheat flour; wheat functionality

Impact of non-thermal plasma on the abatement of Perfluorinated compounds present in minute quantities in water effluents - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Fedorova, Nataliia; Poser, Alexander; Swoboda, Peter; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Based on the strongest C-F bonds backbone, Perfluorinated compounds (PFCs) are manmade chemicals that are omnipresent due to their immense use for the production of various products. Currently, these are also addressed as global contaminants, and are present on the word market since middle of the 20 th century. Non biodegradability and high half-life times generate serious adverse effects on humans and wild life. This calls for remediation. Updated lifetime health advisory, and water quality standards have been issued for PFCs by different US and European environmental agencies, but the conventional techniques for remediation are either inefficient, or turn out to be uneconomic, especially dealing with extremely minute quantities present in effluents. The present study copes with the reduction/removal of low concentrated (<1 μg/l) PFCs from waste water, using non-thermal atmospheric plasma (NTAP). The research experimentally investigates influences of different parameters e.g. plasma gases (air, O2 and N2), treatment times (up to 10 min.) and nozzle/reactor sizes on the reduction of PFC concentrations. Promising results were obtained with NTAP exposure on the PFC concentration levels. In less than 200 seconds, the concentration thresholds of below 50% of initial PFCs concentration was reached in most of the tests within the shown experimental setup. The final concentration of PFCs was strongly dependent on the tested parameters. The decreasing pH value of the water was found to be a limiting factor for the lower PFCs concentration threshol
Keywords: Non-thermal atmospheric plasma; PFC removal; waste water treatment

Influence of Non-Thermal Plasma Treatment on Structural Network Attributes of Wheat Flour and Respective Dough - Khan, Muhammad Jehanzaib; Jovicic, Vojislav; Zbogar-Rasic, Ana; Zettel, Viktoria; Delgado, Antonio; Hitzmann, Bernd (Foods, 2023)
Due to its “generally recognized as safe status” (GRAS) and moderate treatment temperatures, non-thermal plasma (NTP) has lately been considered a suitable replacement for chemicals in the modification of food properties and for preserving food quality. One of the promising areas for the application of NTP is the treatment of wheat flour, leading to improved flour properties and product quality and consequently to higher customer satisfaction. In the present research, the German wheat flour type 550, equivalent to all-purpose flour, was treated using NTP in a rotational reactor to determine the influence of short treatment times (≤5 min) on the properties of flour (moisture and fat content, protein, starch, color, microbial activity, and enzymes), dough (visco-elastic properties, starch, wet and dry gluten, and water absorption), and baking products (color, freshness, baked volume, crumb structure, softness, and elasticity). Based on the properties of NTP, it was expected that even very short treatment times would have a significant effect on the flour particles, which could positively affect the quality of the final baking product. Overall, the experimental analysis showed a positive effect of NTP treatment of wheat flour, e.g., decreased water activity value (<0.7), which is known to positively affect flour stability and product shelf life; dough stability increased (>8% after 5 min. treatment); dough extensibility increased (ca. 30% after 3 min treatment); etc. Regarding the baking product, further positive effects were detected, e.g., enhanced product volume (>9%), improved crumb whiteness/decreased crumb yellowness, softening of breadcrumb without a change in elasticity, and limited microorganism and enzymatic activity. Furthermore, no negative effects on the product quality were observed, even though further food quality tests are required. The presented experimental research confirms the overall positive influence of NTP treatment, even for very low treatment times, on wheat flour and its products. The presented findings are significant for the potential implementation of this technique on an industrial level.
CRIS-Team Scopus Importer:2023-06-09
Keywords: cold plasma; dough rheology; hydration; microbial activity; microstructure; protein and starch properties; wheat flour

Investigation of the Concepts to Increase the Dew Point Temperature for Thermal Energy Recovery from Flue Gas, Using Aspen® - Fedorova, Nataliia; Aziziyanesfahani, Pegah; Jovicic, Vojislav; Zbogar-Rasic, Ana; Khan, Muhammad Jehanzaib; Delgado, Antonio (Energies, 2019)
Thermal energy of flue gases (FG) dissipating from industrial facilities into the environment, constitute around 20% of the total dissipated thermal energy. Being part of the FG, water vapour carries thermal energy out of the system in the form of the latent heat, which can be recovered by condensation, thus increasing the overall efficiency of an industrial process. The limiting factor in this case is the low dew point temperature (usually 40–60 °C) of the water vapour in the FG. The increase of the dew point temperature can be achieved by increasing the water content or pressure. Taking these measures as a basis, the presented work investigated the following concepts for increasing the dew point temperature: humidification of the flue gas using water, humidification using steam, compression of the FG and usage of the steam ejector. Modelling of these concepts was performed using the commercial software Aspen®. The humidification of the FG using water resulted in the negligible increase in the dew point (3 °C). Using steam humidification the temperatures of up to 92 °C were reached, while the use of steam ejector led to few degrees higher dew point temperatures. However, both concepts proved to be energy demanding, due to the energy requirements for the steam generation. The FG compression enabled the achievement of a 97 °C dew point temperature, being both energy-efficient and exhibiting the lowest energy cos
Keywords: thermal energy recovery; flue gas; dew point temperature; condensation; Aspen®